Ảnh hưởng của cacbon hữu hòa tan đến sự rửa giải các nguyên tố trong đất ruộng bị ngập - Hà, Trịnh Thu; Strowble, Bjarne W.; Trung, Nguyễn Quang; Giang, Lê Trường (Vietnam Journal of Chemistry, 2016)
Elements release from initial soil column into flooding water was studied under oxidized and reduced condition, and combining with added dissolve organic carbon in flooding water. When dissolve organic carbon presented in flooding water, element release as Cr, Pb, Ni, As, Co, Al, Cu were increased in both under condition oxidized and reduced. Pb, As, Co and Sb release were highest under reduced condition comparing under oxidized condition, meanwhile, meanwhile Cr, Cu and Al release were highest under oxidized condition.